TRANSFORMASI LITERASI DINI: PRAKTIK MEMBACA NYARING BERBASIS BUKU AUDIO DIGITAL SEBAGAI SARANA PEMANTAPAN FONOLOGI ANAK USIA DINI - Andi Saadillah; Andi Ulfianti; Nur Intan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Phonological skills are the main foundation of early literacy, which plays an important role in the reading and writing readiness of early childhood. Phonological awareness, such as the ability to recognize phonemes and syllables, can be developed through various strategies. One method that has been proven effective in developing phonological awareness is reading aloud. In this activity, educators read books to children with appropriate intonation, emphasis, and expressions that bring the text to life. In the context of technological developments and digital learning, conventional approaches need to be adapted to be more engaging and in line with the learning characteristics of today's children. A potential form of transformation is the use of digital audiobooks in reading aloud activities. This medium is believed to enrich children's listening experience and increase their interest in the text being read. By utilizing sound technology and professional narration, digital audio books can strengthen the sound and rhythm aspects of children's stories. The research method used a descriptive qualitative approach. Data collection techniques included participatory observation, interviews, and documentation. The results of the study show that audiobook-based reading aloud practices are effective in increasing children's engagement and facilitating teachers in phonological learning. Children showed significant phonological development, especially in imitating sounds, repeating words, and recognizing rhymes.  The child-teacher-media interaction showed a new dynamic, namely that digital media can trigger courage, curiosity, and cooperation among children.